2021
DOI: 10.1002/pmic.202000279
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry‐based proteomic platforms for better understanding of SARS‐CoV‐2 induced pathogenesis and potential diagnostic approaches

Abstract: While protein–protein interaction is the first step of the SARS‐CoV‐2 infection, recent comparative proteomic profiling enabled the identification of over 11,000 protein dynamics, thus providing a comprehensive reflection of the molecular mechanisms underlying the cellular system in response to viral infection. Here we summarize and rationalize the results obtained by various mass spectrometry (MS)‐based proteomic approaches applied to the functional characterization of proteins and pathways associated with SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Martinez et al, found higher levels of EGFR in COVID-19 individuals vs. community associated pneumonia subjects (19) and osimertinib, a well-known EGFR antagonist, showed in vitro anti-SARS-CoV-2 action (22) and prevented the virus cytopathic effect (23). In addition, several phosphoproteomic studies of SARS-CoV-2-infected cells disclosed that the virus activates EGFR (24). According Camara and Brandao, EGFR is the main influential receptor involved in COVID-19 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al, found higher levels of EGFR in COVID-19 individuals vs. community associated pneumonia subjects (19) and osimertinib, a well-known EGFR antagonist, showed in vitro anti-SARS-CoV-2 action (22) and prevented the virus cytopathic effect (23). In addition, several phosphoproteomic studies of SARS-CoV-2-infected cells disclosed that the virus activates EGFR (24). According Camara and Brandao, EGFR is the main influential receptor involved in COVID-19 (25).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of a high-throughput, routine, diagnostic clinical setting, a viral infection diagnostic tool should consist of an integrated analytical platform, which needs to be fast, sensitive, highly specific, reproducible, and cost-effective. MS techniques have rapidly complemented or replaced conventional methods in clinical diagnostic laboratories and have been successfully implemented in the investigation of viruses and their pathogenesis [17,[21][22][23][24][25][26][27][97][98][99]. In particular, MALDI-MS has become an indispensable and versatile method for biochemical and clinical investigations [100,101].…”
Section: Biomolecular Host Profiling Approach For Sars-cov-2 Detection By Maldi-msmentioning
confidence: 99%
“…In the last decade or even in recent years, numerous reviews focusing on the use of various MS-based methods in clinical microbiology for the detection of different types of pathogens have been published; most of these reviews concentrated on bacterial pathogens and only marginally covered viral pathogens. 29–33 However, with the advent of the COVID-19 pandemic crisis, the literature has been expanded with reviews on the use of MS-based methods for the study and detection of SARS-CoV-2. Recently, reviews on various MS-based strategies for determining the impacts of COVID-19-infection on host cells have been reported.…”
Section: Introductionmentioning
confidence: 99%